Relations of religion with depression and loneliness in older sexual and gender minority adults. Issue 2 (15th March 2019) - Escher, Catherine; Gomez, Rowena; Paulraj, Selvi; Ma, Flora; Spies-Upton, Stephanie; Cummings, Carlton; Brown, Lisa M.; Thomas Tormala, Teceta; Goldblum, Peter
ABSTRACT: Objectives : High levels of religious involvement have been associated with positive mental health outcomes in older adults. This study investigated whether the effects of religion on healthy aging could generalize to older LGBTQ adults. Methods : This study examined religious affiliation in childhood versus at present, as well as the relationships of outness to religious community and religious engagement with depression and loneliness in 102 lesbian, gay, and bisexual cisgender, transgender, and questioning adults (LGBTQ) over the age of 55. As part of a larger study, participants completed several questions and measures including: one outness to religious community item, 4 religious engagement questions, the Center for Epidemiological Studies Depression Scale, and the 8-item UCLA Loneliness Scale. Results : Many older LGBTQ adults reported changes in religious affiliation from childhood to adulthood. Greater levels of outness to religious communities and lower religious engagement were related to lower levels of depression and loneliness. Conclusions : Findings suggest that outness to religious communities may be beneficial to the mental health of older LGBTQ adults. Higher levels of distress may lead to higher levels of religious engagement. Clinical Implications : Religion, especially those that are supportive of sexual minorities, may help to improve the well-being of older LGBTQ adults.